MAKANAN ADAT MANJAPUIK MARAPULAI PADA ACARA PERKAWINAN DI NAGARI MUNGKA KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - Dahnia, Whustoh; Baidar, Baidar; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2017)
The purpose of this study are to (1) describe the implementation of traditional events of Manjapuik Marapulai,(2) to identify custom food types, (3) to describe the equipment used to bring food, (4) to express the meaning in the food brought Manjapuik Marapulai ceremony. This is qualitative research, research location in Nagari Mungka, with interviewee Bundo Kanduang, Niniak Mamak, and community. Data collection techniques are observation, interview and documentation. Data analysis techniques are data reducation, data persentation and conclusion or verification. The results showed that, Manjapuik Marapulai event was held on baralek day at the time agreed by both families. Traditional food consists of 1 bowl of white rice, 2 chunks of meat curry, 2 chopped coconut curry, 2 fried fish,3 pieces of meat rendang, 1 duck eggs, 2 galamai, 2 wajik, 2 plate of rice lomak, 2 plate of rice rendang, 1 plate of ompiang ajik, 1 luwo dish,4 paniaram, 1sponge cake, 1 agar- agar and 4 banana combs. The equipment used for carrying food are the tuna and its base, katidiang, carano and lid, the flat plate, and the bowl. The meaning of the food is to bond the two families and the married life of daro and marapulai. Keywords: Traditional Food, Manjapuik Marapulai, Nagari Mungka